Gerakan Global Pembebasan Palestina Pasca 'Boikot-Divestasi-Sanksi' - Setyaka, Virtuous; Tursina, Zahidiyah Ela; Ardiyanti, Dwi (Indonesia Center for Middle East Studies, 2025)
The Boycott, Divestment, and Sanctions (BDS) movement emerged as a response to Israel’s settler colonialism, apartheid, and human rights violations against the Palestinian people. While BDS has succeeded in raising global awareness and fostering international solidarity, its effectiveness in achieving structural change remains contested. This article offers a critical reflection on the achievements and limitations of the BDS movement within the context of the global political economy, and proposes an alternative strategy grounded in Coxian critical theory. Emphasizing the role of social forces of production, state formation, and world order, this approach promotes more inclusive and transformational transnational mobilization. It also involves reforming global institutions, building alliances among Global South countries, and leveraging media and technology to construct counter-hegemonic narratives that challenge Israel’s ideological and economic dominance. The article argues that the liberation of Palestine requires a global movement that goes beyond economic tactics, toward a reconstruction of global structures rooted in social justice.